Gender and Initial Teacher Training: Challengers in terms of social justicie - Vallejos , Rosse Marie; Palma, Marcela; Corrales, Angélica (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Under a qualitative-interpretative framework, this study carried out a discourse analysis of future teachers in Chile regarding their training and the integration of the gender variable in terms of inclusion. Based on the previously defined dimensions, categories emerged from the discourse applied to conversation and speech acts. Main conclusions show the awareness of the importance of this perspective in the acknowledgement of diverse classrooms, for which there is intuitive or self-taught knowledge but lack thereof from what was acquired in the initial teacher training.